2013
DOI: 10.1039/c3cc44995e
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium-catalyzed oxidative coupling through C–H activation and annulation directed by phosphonamide and phosphinamide groups

Abstract: Rhodium-catalyzed oxidative coupling reactions via C-H activation and annulation directed by phosphonamide and phosphinamide groups were developed under aerobic conditions, which produced benzazaphosphole 1-oxides and phosphaisoquinolin-1-oxides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 102 publications
(31 citation statements)
references
References 43 publications
0
31
0
Order By: Relevance
“…To shed more light on the reaction mechanism, a deuterium‐labeling experiment was were performed (Scheme ) 12. 16a When a 1:1 mixture of 1 a and 1 a‐[D 5 ] was subjected to the Rh‐catalyzed reaction conditions, we obtained the cyanation products 3 a and 3 a‐[D 4 ] in a ratio of 4.9:1. This kinetic isotope effect (KIE) value of 4.9 is typical of Rh‐catalyzed CH activation processes.…”
Section: Methodsmentioning
confidence: 99%
“…To shed more light on the reaction mechanism, a deuterium‐labeling experiment was were performed (Scheme ) 12. 16a When a 1:1 mixture of 1 a and 1 a‐[D 5 ] was subjected to the Rh‐catalyzed reaction conditions, we obtained the cyanation products 3 a and 3 a‐[D 4 ] in a ratio of 4.9:1. This kinetic isotope effect (KIE) value of 4.9 is typical of Rh‐catalyzed CH activation processes.…”
Section: Methodsmentioning
confidence: 99%
“…During their investigation on annulation reaction between phosphonamide and activated alkenes or alkynes, Lee and coworkers also demonstrated that phosphonamide can act as a directing group in Rh(III)-catalysed ortho-alkenylation with styrenes even in the presence of TEMPO (Scheme 10). 18 The reaction was found to be sluggish with non-activated alkenes and only mono-alkenylation occurred even in the presence of access amount of styrene derivatives. In 2017, our group reported the first example of orthoalkenylation with alkenes of triarylphosphine oxides using Ru(II) catalyst (Scheme 11).…”
Section: Scheme 8 Rh(iii)-catalysed Ortho-alkenylation Of Aryl Phospmentioning
confidence: 97%
“…Encouraged by the our previous results,4b the most efficient catalysis was achieved with alkenylphosphonic monoesters, which also allowed the synthesis of phosphorus 2‐pyrones (Scheme ).…”
Section: Introductionmentioning
confidence: 98%